Tailored Peptide Phenyl Esters Block ClpXP Proteolysis by an Unusual Breakdown into a Heptamer–Hexamer Assembly. Issue 21 (17th April 2019) - Lakemeyer, Markus; Bertosin, Eva; Möller, Friederike; Balogh, Dóra; Strasser, Ralf; Dietz, Hendrik; Sieber, Stephan A.
Abstract: The proteolytic complex ClpXP is fundamental to bacterial homeostasis and pathogenesis. Because of its conformational flexibility, the development of potent ClpXP inhibitors is challenging, and novel tools to decipher its intricate regulation are urgently needed. Herein, we present amino acid based phenyl esters as molecular probes to study the activity and oligomerization of the ClpXP complex of S. aureus . Systematic screening of ( R )‐ and ( S )‐amino acids led to compounds showing potent inhibition, as well as stimulation of ClpXP‐mediated proteolysis. Substoichiometric binding of probes arrested ClpXP in an unprecedented heptamer–hexamer assembly, in which the two heptameric ClpP rings are dissociated from each other. At the same time, the affinity between ClpX and ClpP increased, leading to inhibition of both enzymes. This conformational arrest is beneficial for the consolidated shutdown of ClpXP, as well as for the study of the oligomeric state during its catalytic cycle. Abstract : Tight and loose : Covalent ( R )‐amino acid modifiers are novel tools for probing the activity and oligomerization of the bacterial ClpXP protease. Substoichiometric binding strengthens the ClpX–ClpP interaction. Depending on the substitution of the compound, proteolysis is either stimulated or efficiently inhibited by formation of an unprecedented complex assembly.